Organizational Communication Analysis on Work Performance and Organizational Commitment to Student and Lecturer Satisfaction at the STIAMI Institute - Pangestu, Danang Aji; Indahsari, Tri; Alifah, Ria; Berliana, Vikky; Suwarta, Firdaus; Razali, Geofakta (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of organizational communication on work performance, organizational commitment, and student and lecturer satisfaction at the STIAMI Institute. A qualitative approach with case studies is used, and the variables tested include internal communication, openness, participation, recognition, and interpersonal communication. Survey methods and academic consultants are applied to strengthen communication and improve the teaching quality of lecturers. The results of the research show the importance of organizational communication in building a harmonious relationship between lecturers and students. This study recommends increasing the acceptance of input from students by lecturers, strengthening communication programs, maintaining the quality of interaction between lecturers and students, and improving services to students. The implication is increasing the effectiveness of organizational communication which has an impact on work performance, organizational commitment, and satisfaction of lecturers and students within the STIAMI Institute